An "IGERT" Model for Interdisciplinary Doctoral Education in Water‐Related Science and Policy. (March 2013) - Pinter, Nicholas; Baer, Sara; Chevalier, Lizette; Kowalchuk, Rhonda; Lant, Christopher; Whiles, Matt
Abstract Most doctoral programs in the U.S. remain "stove‐piped" in traditional single‐discipline fields, while scientific progress increasingly occurs at the boundaries between multiple disciplines. In response, the U.S. National Science Foundation has been funding projects in Integrative Graduate Education, Research, and Training (IGERT) to train a new generation of interdisciplinary scientists. The IGERT Ph.D. program in "Watershed Science and Policy" at Southern Illinois University (SIU) builds each year's student class as a diverse "cadre" who work intensively together on one hot‐button river basin. The structure of these projects, and other program elements, are reviewed here along with successes and challenges to date. One challenge is the seeming tradeoff between (1) the development of tightly focused expertise versus (2) the breadth that characterizes interdisciplinary research. We conclude that interdisciplinary scientists must have disciplinary depth, but so too should they be trained in collaboration and integrating their results to address the challenges that face today's complex world.